Effects of Stocking Density on Growth Performance, Antioxidant Status, and Meat Quality of Finisher Broiler Chickens under High Temperature - Jiseon Son; Hee-Jin Kim; Eui-Chul Hong; Hwan-Ku Kang (MDPI AG, 2022)
Environmental factors such as stocking density and high temperature can cause oxidative stress and negatively affect the physiological status and meat quality of broiler chickens. Here, we evaluated the effects of heat stress on the growth performance, antioxidant levels, and meat quality of broilers under different stocking densities. A total of 885 28-day-old male broilers (Ross 308) were subjected to five treatments (16, 18, 21, 23, and 26 birds/m2) and exposed to high temperatures (33 °C for 24 h) for 7 days. High stocking density (23 and 26 birds/m2) resulted in significantly decreased body weight (p < 0.01) and superoxide dismutase activity in the blood (p < 0.05) and increased (p < 0.05) rectal temperature and corticosterone. Additionally, the concentrations of heat shock protein 70 and malondialdehyde in the liver were higher in the 26 birds/m2 group (p < 0.05). Similarly, the 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity of breast meat increased linearly as the stocking density increased (p < 0.05). There was increased shear force in breast meat at low stocking density (p < 0.01). Thus, lower stocking density can relieve oxidative stress induced by high temperatures in broilers and improve the antioxidant capacity and quality of breast meat during hot seasons.